2018
DOI: 10.5296/npa.v9i3-4.12319
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned Aerial Vehicular System for Greenhouse Gas Measurement and Automatic Landing

Abstract: This paper presents a reliable and low cost greenhouse gas measurement system. The system mainly consists of an unmanned aerial vehicle (UAV), a set of calibrated sensors, a wireless system, and a microcontroller. The system can measure the concentration of greenhouse gases namely carbon dioxide (CO 2 ), methane (CH 4 ), and ozone (O 3 ) at different altitudes. It can also measure temperature, humidity, and atmospheric pressure. The system is able to send data to a remote monitoring station. The UAV is equippe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In terms of perspective, in our future work, we hope to validate our algorithms with real data, to check if our algorithms control the greenhouse's internal climate. We also plan to add other parameters such as air quality as in [21] and consider other types of farming such as hydroponic farming as in [22]. Finally, for the system to be controlled remotely our future investigations will be on the development of the LoRaPAN communication.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of perspective, in our future work, we hope to validate our algorithms with real data, to check if our algorithms control the greenhouse's internal climate. We also plan to add other parameters such as air quality as in [21] and consider other types of farming such as hydroponic farming as in [22]. Finally, for the system to be controlled remotely our future investigations will be on the development of the LoRaPAN communication.…”
Section: Resultsmentioning
confidence: 99%
“…For this test, two anemometers were placed at ten distances from 0.52 m to 3.48 m beneath the UAV rotors. Of the eighteen found papers that use a UAVmounted gas monitor, four placed the measuring point above the UAV (Alvarado et al, 2017;Brady et al, 2016;Roldan et al, 2015;Zhou et al, 2017), three placed the measuring point horizontally from the UAV (Villa et al, 2016;2019), and twelve placed the measuring point beneath the UAV (Aboubakr et al, 2017;Ali et al, 2017;Aurell et al, 2017;Barchyn et al, 2018;Chang et al, 2016Chang et al, , 2018Gu et al, 2018;Liu et al, 2018;McCray, 2016;Neumann, 2013;Smidl and Hofman, 2013;Yao et al, 2018). Gas monitor placement beneath the UAV appears in 63% of found papers, which implies this as the most popular configuration.…”
Section: Test Proceduresmentioning
confidence: 99%
“…Smidl and Hofman (2013) published one of the first papers to discuss using UAVs to measure gas concentrations, though the discussion was purely theoretical. Since then, four more papers were found discussing theoretical applications of UAV-mounted gas monitors (Alvear et al, 2017;Bolla et al, 2018;Nash, 2017), and six papers were found to actually attempt data collection (Aboubakr et al, 2017;Ali et al, 2017;Barchyn et al, 2018;Chang et al, 2016Chang et al, , 2018Liu et al, 2018). However, none of these papers discussed the potential measurement errors inherent with using such a system.…”
Section: Introductionmentioning
confidence: 99%